GENDER EQUALITY IN GOVERNANCE: IMPERATIVES FOR DEMOCRACY AND DEVELOPMENT IN NIGERIA - Bekeh Undie, Joseph; Isomkwo Aboh, Fidelis; Etianghe Omang, Cornelius (African Journal of Social and Behavioural Sciences, 2025)
This paper examines the critical role of gender equality in governance as a pathway to sustainable democracy and development in Nigeria. There is still, in perpetuation, gender bias in governance. This is largely due to the existing socio-cultural structure and practices that perpetuate anti-democratic ideals and hinder development in our contemporary world. Undoubtedly, these practices, which are self-injurious and retrogressive, terribly place women in a questionable incapacitation that makes them unable to harness their latent endowment for their benefit and the society at large. This has made it imperative to advocate for a departure from this archaic, primordial, and non-progressive practice of not allowing them to offer what they have in complementarity. Consequently, the paper focused on the plight of women in governance/political leadership; participation of women in governance/political leadership; patriarchy and other factors militating against women’s participation in governance/political leadership; arguments against women’s participation in governance/political leadership; and arguments for women’s participation in governance/political leadership and strategic ways to encourage and increase women’s participation in governance/political leadership